"It doesn't include us": Heterosexual bias and gay men's struggle to see themselves in affirmative consent policies. Issue 1 (1st December 2021) - Richardson, Jacob W.
Abstract: Rape and sexual assault are considered forms of gender violence, or violence against women, and affirmative consent policies were created as a primary prevention strategy to combat this kind of sexual violence on college and university campuses. Such policies are often promoted as being inclusive and applicable cross‐culturally because of the gender‐neutral language within affirmative consent policies; however, the highly gendered nature of sexual assault discourse has become hegemonic and thereby unintentionally reinforces a heterosexually gendered false dichotomy about sexual violence. This qualitative study utilizes in‐depth interviews with 10 gay men to explore how they perceive affirmative consent policies. The results found that gay men perceived an implicit heterosexual bias within affirmative consent policies that reinforced heterosexist conceptions of sex, gender, sexual scripts, and sexual assault. Ultimately, this made it challenging for participants to see themselves in affirmative consent policies. Moreover, it burdens gay men whose experiences with sex and consent, as well as sexual assault, do not fit within the heterosexist paradigm of current sexual assault and affirmative consent discourses/policies. Resumen: La violación y la agresión sexual se consideran formas de violencia de género o violencia contra la mujer, y se crearon políticas de consentimiento afirmativo como estrategia de prevención primaria para combatir este tipo de violencia sexual en los campus universitarios y universitarios. A menudo, estas políticas se promueven como inclusivas y aplicables transculturalmente debido al lenguaje neutral en cuanto al género dentro de las políticas de consentimiento afirmativo; sin embargo, la naturaleza altamente sexista del discurso sobre la agresión sexual se ha vuelto hegemónica y, por lo tanto, refuerza involuntariamente una falsa dicotomía de género heterosexual sobre la violencia sexual. Este estudio cualitativo utiliza entrevistas en profundidad con 10 hombres homosexuales para explorar cómo perciben las políticas de consentimiento afirmativo. Los resultados encontraron que los hombres homosexuales percibían un sesgo heterosexual implícito dentro de las políticas de consentimiento afirmativo que reforzaban las concepciones heterosexistas de sexo, género, guiones sexuales y agresión sexual. En última instancia, esto hizo que fuera un desafío para los participantes verse a sí mismos en las políticas de consentimiento afirmativo. Además, agobia a los hombres homosexuales cuyas experiencias con el sexo y el consentimiento, así como la agresión sexual, no encajan dentro del paradigma heterosexista de los discursos/políticas actuales de agresión sexual y consentimiento afirmativo. 摘要: 强奸和性侵犯被视为性别暴力或针对女性的暴力形式, 并且性同意 (affirmative consent) 政策的出现被作为打击这类校园性暴力的主要预防策略。这类政策因其所使用的性别中立语言而经常被宣传为具有包容性, 并能应用于不同文化；不过, 性侵犯话语的高度性别化性质已占据支配地位, 因此无意加强了基于异性恋的、错误的性暴力二分法。本定性研究对10名男同性恋进行深度访谈, 以期探究他们如何感知性同意政策。结果表明, 男同性恋从性同意政策中感知了隐含的异性恋偏见, 这种偏见加强了异性恋主义对性行为、社会性别、性规范 (sexual scripts) 和性侵犯的构想。最终, 这对参与者认可性同意政策一事造成困难。此外, 这对男同性恋造成负担, 他们在性行为和性同意以及性侵犯方面的经历不符合当前性侵犯和性同意话语/政策的异性恋主义范式。